2019
DOI: 10.1101/585166
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and characterization of phytosterol nanoemulsions and self-microemulsifying drug delivery systems

Abstract: The aim of this study is to develop a self microemulsion drug delivery system for phytosterols to improve the solubility and bioavailability. The results showed that the formulation of phytosterol self-microemulsion is: lemon essential oil in oil phase, polyoxyethylene hydrogenated castor oil 40 and Tween 60 in emulsifier, polyethylene glycol 400 in co-emulsifier, Km = 7:3, Kp = 3:1, Ke = 50%. The drug loading of phytosterol self-microemulsion prepared by this method was 87.22 mg/g, encapsulation efficiency wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…14 Yuan et al (2019) reported that β-sitosterols in the microemulsion (emulsifier: polyoxyethylene hydrocastor oil 40 : tween 60 = 7 : 3, m/m, co-emulsifier : polyethylene glycol 400, emulsifier : co-emulsifier = 3 : 1, m/m, 33% lemon essential oil) increased the bioavailability more than 3 times that of commercial crystallized powder of β-sitosterols. 45 In another study, these researchers also reported that a β-sitosterol self-microemulsion has higher hypolipidemic efficiency than a sitosterol ester with linoleic acids, β-sitosterol healthy tablets and β-sitosterol powder, dissolved in tea seed oil. 46…”
Section: Delivery Systems For Phytosterolsmentioning
confidence: 97%
“…14 Yuan et al (2019) reported that β-sitosterols in the microemulsion (emulsifier: polyoxyethylene hydrocastor oil 40 : tween 60 = 7 : 3, m/m, co-emulsifier : polyethylene glycol 400, emulsifier : co-emulsifier = 3 : 1, m/m, 33% lemon essential oil) increased the bioavailability more than 3 times that of commercial crystallized powder of β-sitosterols. 45 In another study, these researchers also reported that a β-sitosterol self-microemulsion has higher hypolipidemic efficiency than a sitosterol ester with linoleic acids, β-sitosterol healthy tablets and β-sitosterol powder, dissolved in tea seed oil. 46…”
Section: Delivery Systems For Phytosterolsmentioning
confidence: 97%
“…Furthermore, an optimization of drug dosage can be conducted for other animals as well. Chuanxun et al (2019) prepared self-microemulsions for phytosterols using the lemon essential oil as oil phase, polyoxyethylene hydrogenated castor oil 40, and Tween 60 as emulsifiers, and polyethylene glycol 400 as co-emulsifier. Encapsulation efficiency of 89.65% was achieved and the drug loading of phytosterol self-microemulsion was 87.22 mg/g.…”
Section: Emulsification Techniquementioning
confidence: 99%
“…Their incorporation into nanoemulsions can help overcome this issue. Chuanxun et al [ 360 ] proved the reduction of oxidation degradation of phytosterols caused during storage by using nanoemulsions while Acevedo-Estupiñan et al [ 361 ] prepared phosphatidylcholine and lysophosphatidylcholine nanoemulsions incorporating phytosterols and achieved the increase of their chemical stability as well as their water solubility. Borba et al [ 362 ] prepared β-carotene nanoemulsions by high-pressure homogenization, with an average size of 300 nm [ 362 ].…”
Section: Organic-based Delivery Systemsmentioning
confidence: 99%